The Mackenzie Inuit Winter House - Arnold, Charles D.; Hart, Elisa J. (ARCTIC, 1992)
The Inuit of the Mackenzie Delta area who called themselves "Siglit", built winter homes not out of snow, but of driftwood, and in villages which they occupied annually. This article discusses the earliest historical record of Siglit architecture and building techniques including ventilation and insulation.